Social Media Effectiveness and Employee Recruitment in Indonesian State-Owned Enterprises: The Mediating Role of Informativeness - Meutia Dwi Novita Sari; Burhanis Sulthan; Hendra Halim (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study asks whether the effectiveness of social media used by Indonesian state-owned enterprises (SOEs/BUMN) in Aceh improves recruitment process quality, and whether this relationship operates through perceived informativeness of recruitment content. The issue is salient in Aceh’s constrained formal labor market and strong demand for SOE jobs, which heightens the need for transparent, efficient, and credible digital recruitment communication. The novelty of this paper lies in providing region-specific empirical evidence for SOE e-recruitment in Aceh while explicitly testing an information-mediating mechanism. Using a quantitative survey of 306 employees across approximately 12 SOEs in Aceh (recruited in 2020–2024 and informed via Instagram, LinkedIn, or Facebook), data were analyzed with PLS-SEM and bootstrapping to estimate direct and indirect effects. Results show that social media effectiveness positively affects recruitment process quality and informativeness, while informativeness also improves recruitment process quality. The indirect effect is significant, indicating partial mediation, and the model explains 47.6% of informativeness and 59.6% of recruitment process variance.